2021
DOI: 10.1097/der.0000000000000790
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Patch Testing With Shoe Material Samples in Patients Suspected of Shoe Allergic Contact Dermatitis

Abstract: Background: Patch testing is the standard diagnostic tool for shoe allergic contact dermatitis (ACD). As shoe materials change over time, utilizing commercial allergen series might be ineffective. However, because testing with patients' shoe samples is laborious, its value is questioned.Objective: The aim of this study was to ascertain the benefits of patch testing with patients' shoes by comparing the frequencies of patch-test positivity of shoes and shoe-related allergens in baseline series for suspected sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Patch testing with shoe pieces plays a crucial role in detecting footwear ACD, as exemplified by our previous study that demonstrated a 37.7% increase in diagnostic yield through such testing with shoe materials 8 . In the current investigation, almost a quarter of the patients showed a positive reaction when patch tested with shoe pieces.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Patch testing with shoe pieces plays a crucial role in detecting footwear ACD, as exemplified by our previous study that demonstrated a 37.7% increase in diagnostic yield through such testing with shoe materials 8 . In the current investigation, almost a quarter of the patients showed a positive reaction when patch tested with shoe pieces.…”
Section: Discussionsupporting
confidence: 61%
“…For shoe pieces, thin pieces of shoes at the area of correlated dermatitis were cut to approximately 1 cm 2 and soaked in water for 15 min 8 . The placement was on the upper arm using surgical tape (3 M Blenderm, Borken, Germany) for 4 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation